TEKNOLOGI TEPAT GUNA SEDERHANA PENGELOLAAN AIR JERNIH DI DESA WISATA SUMBERGEDANG PASURUAN - Harmi Tjahjanti, Prantasi; -, Iswanto; Fahruddin, A'rasy; Ryan Ernanda, Rico (Jurnal Abdimas ADPI Sains dan Teknologi, 2021)
During the Covid-19 pandemic, the tourist village of Sumbergedang, Pandaan Pasuruan, experienced a drastic decrease in visitors, which greatly reduced their income. Meanwhile, in the village, water from the mountains is very abundant. Purpose and solution offered is to manage clear water in the village using Simple Appropriate Technology, namely making a tubing tube to fill the clear water which will later be processed into clean water. The clean water produced is ready to drink, and this will be a separate effort to increase the income of residents in the tourist village of Sumbergedang during the Covid-19 pandemic